Impact of SNS Behavior on Social Commerce Purchase Intention: Focusing on the Mediating Effect of Social Capital - Ofori, Henry; Kang, Juyoung (International Journal of Software Innovation, 2022)
Social commerce, a subset of eCommerce that usually occurs on social media platforms, is currently revolutionizing eCommerce. Activities undertaken on SNS such as posting, commenting, liking, sharing, and reading on SNS have been described by literature to lead to sharing and giving social commerce-related information. But no study has focused on whether these SNS activities may influence purchase intention. As such, this paper sought to assess the influence of two main forms of SNS behavior (active and passive SNS behavior) on social commerce purchase intention as well as examine the mediating effect of online bridging and bonding social capital. The results further revealed that active SNS behavior has a positive influence while passive SNS behavior has a negative influence on purchase intention under social commerce. The results and contribution of this study regarding theory, practice, and future research are further discussed.
Keywords: Active and Passive Social Network Site (SNS) Behavior; Online Bonding and Bridging Social Capital; Social Commerce Purchase Intention